Cæsar som nietzscheansk motiv. En editionsfilologisk undersøgelse af Henrik Pontoppidans Lykke-Per - Gottlieb, Katja (Danske Studier, 2026)
In December 1904 the last volume of the first edition of the Danish author Henrik Pontoppidan’s masterpiece Lykke-Per (Eng.: Lucky Per) was published. On the last page the author informed the reader that a new, revised and slightly abbreviated version of Lykke-Per would soon be published, and the author requested that this new edition be used as a basis for a future assessment of the overall work. The revised version of Lykke-Per became available for purchase a few months later, but in 1918 Pontoppidan chose to publish yet another abridged and revised edition of the work. While working on the first edition, Pontoppidan became preoccupied with studies in German philosopher Friedrich Nietzsche, whose philosophy came to influence Lykke-Per. In Lykke-Per Pontoppidan uses Nietzsche’s thoughts of ‘the will to power’ and his homage to the heroic figures of history, such as Caesar, as consistent themes, and the influence can be traced through the different versions of Lykke-Per. The tools of scholarly editing can map out this inspiration from Nietzsche, thus providing the reader with valuable insight in the transformation of the motifs of Lykke-Per through the different versions.